2012
DOI: 10.3343/alm.2012.32.3.210
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis C Virus Infections and Distribution of Hepatitis C Virus Genotypes among Korean Blood Donors

Abstract: BackgroundHepatitis C virus (HCV) remains a worldwide health-care burden. Prevalence rates vary and the distribution of genotypes depends on geographical location. Here, the recent prevalence of HCV infections and distribution of HCV genotypes among Korean blood donors were studied.MethodsBetween February 2005 and December 2009, a total of 11,064,532 donors were screened for anti-HCV and 11,412,690 donors were screened for HCV RNA. HCV genotyping was conducted for 748 blood donors with HCV RNA by using the lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 21 publications
2
14
1
Order By: Relevance
“…The Genotype 3a was the predominant genotype in this study, which is in line with the findings of studies conducted in India, Pakistan and Nepal (13,14). However, these findings are inconsistent with the results of studies in Saudi Arabia (15), Kuwait (16), France (17), North American countries (18) and South Korea (19). This difference could be due to high prevalence of intravenous drug abuse in the present study (48.33%) because numerous molecular epidemiological studies suggest an association between genotype 3a transmission and history of intravenous drug abuse (13,16,20).…”
Section: Discussioncontrasting
confidence: 42%
“…The Genotype 3a was the predominant genotype in this study, which is in line with the findings of studies conducted in India, Pakistan and Nepal (13,14). However, these findings are inconsistent with the results of studies in Saudi Arabia (15), Kuwait (16), France (17), North American countries (18) and South Korea (19). This difference could be due to high prevalence of intravenous drug abuse in the present study (48.33%) because numerous molecular epidemiological studies suggest an association between genotype 3a transmission and history of intravenous drug abuse (13,16,20).…”
Section: Discussioncontrasting
confidence: 42%
“…In addition, several previous small-scale studies reported that genotypes 1b (about 50%) and 2a/c (about 50%) were dominant in Korea 6,8. A recent study of the HCV genotypes in Korean blood donors found genotypes 1b, 1a , 2a/c, 2b, 3a, and 4 in 47.7, 1.3, 35.0, 2.3, 1.6, and 0.1%, respectively, but none with genotype 6 9. In comparison, in this study, 1% of the chronic liver disease patients were infected with genotype 6 HCV, confirming the rarity of this genotype in Korea.…”
Section: Discussionmentioning
confidence: 97%
“…The highest seroprevalence of HCV is in those aged ≥70 years; the burden of disease in the elderly Korean population is comparable to the global seroprevalence of HCV (2.31% and 2.35%, respectively) . Genotype 2 has a seroprevalence of 38–46% in Korea . Combination therapy with once‐weekly subcutaneous pegylated interferon‐alpha plus daily oral ribavirin administered for 24 weeks is the standard‐of‐care regimen for the first‐line treatment of Korean patients with chronic genotype 2 HCV infection .…”
Section: Introductionmentioning
confidence: 99%